The Use of AI Writing Assistance for Academic Writing: Investigating the Introduction Section of Research Articles Written by EFL Students - Aini Nabila Ikhwanudin; Bambang Yudi Cahyono; Niamika El Khoiri (Jurnal Pendidikan Bahasa Inggris Undiksha, 2026)
This study investigated the utilization of AI writing assistants by EFL students in constructing the research article introduction section, specifically focusing on the application of Swales’ Create a Research Space (CARS) model. The research aimed to evaluate the extent of AI integration, the rhetorical quality of the introductions, and students’ perceptions of AI-mediated writing. A descriptive qualitative method was employed in this study, involving the analysis of 33 student manuscripts and semi-structured interviews. Data were collected using Turnitin AI detection reports and a rhetorical analysis checklist. The results revealed that while the majority of students demonstrated a strong grasp of establishing a research territory ( Move 1), significant challenges remained in establishing and occupying a niche (Moves 2 and 3). Turnitin analysis indicated that most students utilized AI strategically for linguistic refinement and structural scaffolding, with only a small minority exhibiting high dependence. Furthermore, participants perceived AI as a vital tool for enhancing writing efficiency, coherence, and grammatical accuracy. Based on these findings, it was concluded that AI functions effectively as a pedagogical scaffold that supports systematic writing; however, integrating critical AI literacy is essential to ensure that students maintain authorial agency and avoid uncritical reliance.